European competitiveness: A semi-parametric stochastic metafrontier analysis at the firm level - Michel Dumont; Bruno Merlevede; Glenn Rayp; Marijn Verschelde (National Bank of Belgium, 2014)
In this paper a semiparametric stochastic metafrontier approach is used to obtain insight into firmlevel competitiveness in Europe. We differ from standard TFP studies at the firm level as we simultaneously allow for inefficiency, noise and do not impose a functional form on the input-output relation. Using AMADEUS firm-level data covering 10 manufacturing sectors from seven EU15 countries, (i) we document substantial, persistent differences in competitiveness (with Belgium and Germany as benchmark countries and Spain lagging behind) and a wide technology gap, (ii) we confirm the absence of convergence in TFP between the seven selected countries, (iii) we confirm that the technology gap is more pronounced for smaller firms, (iv) we highlight the role of post-entry growth for competitiveness.
Keywords: C14; D24; L25; M13; O33; 330; competitiveness; cross-country analysis; firm heterogeneity; total factor productivity; post-entry growth; Unternehmen; Internationaler Wettbewerb; Internationaler Markteintritt; Produktivität; Industrie; Vergleich; Nichtparametrisches Verfahren; EU-Staaten